2007
DOI: 10.1111/j.1460-2695.2006.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Laser peening and shot peening effects on fatigue life and surface roughness of friction stir welded 7075‐T7351 aluminum

Abstract: The effects of laser peening, shot peening, and a combination of both on the fatigue life of Friction Stir Welds (FSW) was investigated. The fatigue samples consisted of dog bone specimens and the loading was applied in a direction perpendicular to the weld direction. Several laser peening conditions with different intensities, durations, and peening order were tested to obtain the optimum peening parameters. The surface roughness resulting from various peening techniques was assessed and characterized. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 27 publications
0
29
0
1
Order By: Relevance
“…It was found that the fatigue strength of the FSW weld at 10 7 cycles was lower than that of the base metal [5], but higher than that of traditional fusion welds [3,6]. Further, welding parameters [3,7,8] and surface quality [9,10] of the FSW welds exerted a significant effect on the fatigue strength of the weld, and the fatigue crack growth resistance of the nugget zone was the lowest throughout the FSW weld, due to an intergranular failure mechanism [11]. Generally, the cyclic loading probably extends beyond a million cycles in the working service of aerospace and transport structures [12,13].…”
Section: Introductionmentioning
confidence: 96%
“…It was found that the fatigue strength of the FSW weld at 10 7 cycles was lower than that of the base metal [5], but higher than that of traditional fusion welds [3,6]. Further, welding parameters [3,7,8] and surface quality [9,10] of the FSW welds exerted a significant effect on the fatigue strength of the weld, and the fatigue crack growth resistance of the nugget zone was the lowest throughout the FSW weld, due to an intergranular failure mechanism [11]. Generally, the cyclic loading probably extends beyond a million cycles in the working service of aerospace and transport structures [12,13].…”
Section: Introductionmentioning
confidence: 96%
“…Laser shock peening (LSP) is an emerging competitive alternative to shot peening for imparting compressive residual stresses into the surfaces of components (Rodopoulos et al, 2003;Hatamleh et al, 2007a). LSP provides many advantages over shot peening in that the process can introduce deeper and larger compressive residual stresses, stronger work-hardening surface layer, as well as reduced surface roughness.…”
Section: Laser Shock Peening (Lsp) Vs Shot Peeningmentioning
confidence: 99%
“…from 160,000 to 310,000 (Hatamleh et al, 2007a) when the surface is shock peened twice. Therefore, one Table 1 Operating parameters and material/energy flows involved in shot peening and laser shock peening processes.…”
Section: Inventory Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the contour method, the part is cut into two and the measured contour of the exposed surface is used to calculate stresses. The contour method is useful for studying various manufacturing processes such as laser peening [2][3][4][5], friction stir welding [3 ,4,6] and fusion welding [1 ,7-10]. Some of the applications are quite unique such as mapping stresses in a railroad rail [11], in the region of a individual laser peening pulse [12], and under an impact crater [13].…”
Section: Introductionmentioning
confidence: 99%